Evolving Living Values in an Intergenerational Contexts - Bhattarai, Tikaram (Journal of Research in Education, 2025)
This study examines how living values more especially, cooperation and respect evolve throughout time within the framework of inter- generations. Using narrative inquiry, the study looks at how these values have changed across the generations within extended families. The research attempts to understand how respect and cooperation emerge differently based on age, social expectations, and external influences like globalization and technology advancement by examining interactions among teens, adults, and elderly. It further states respect and cooperation, focuses on how community values have changed over time. Purposive sampling was used to collect data, focusing on three generational groups within extended families in order to gain a variety of viewpoints. The results of the study also demonstrate how the adult generation (20–59) acts as a mediator, adjusting to both conventional and contemporary interpretations of these principles. Younger people see respect as more transactional, whereas the elder generation still understands it as communal and hierarchical. Convenience and mutual gain increasingly eclipse the once viewed social imperative of cooperation, mirroring broader shifts in society. Findings of the study highlight the value of intergenerational communication in preserving and advancing living values. In order to ensure that these values continue to be relevant in a society that is becoming more complicated and diverse, it is suggested that ethical education programs be modified to meet the evolving nature of respect and cooperation. The study adds to the conversation on moral growth and provides information on how moral principles are both maintained and changed through time.